Effect of facemask use on cognitive function during a maximal running aerobic fitness test - Slimani, Maamer; Paravlic, Armin; Abazovic, Ensar; Znazen, Hela; Bragazzi, Nicola Luigi (Frontiers in Physiology, 2022)
Background: The aim of the present study was to determine the cognitive function response while wearing a face mask during a maximal running aerobic fitness test. Methods: Fourteen healthy, non smoking physical education students (age = 17.5 years, height = 1.72 m, body mass = 70.4 kg) volunteered to participate in this study. They were randomized to perform 20 m multistage fitness tests (MSFT) while wearing a cloth face mask (EXP) or no mask (CON) on two separate occasions. Rate of perceived exertion (RPE) and d2 test for attention were assessed before and immediately after MSFT for both conditions. Results: EXP group had lower maximal aerobic speed (km/h) (p = 0.039), VO2max (p = 0.039), number of distances run during MSFT (p = 0.057), and concentration performance (p < 0.001) when compared to CON group. EXP group had more errors compared to the CON group (p = 0.021). The use of a cloth face mask during maximal endurance running tests, such as MSFT, reduced VO2max, and measures of cognitive performance assessed by the test of focused visual attention d2. This data suggests avoiding a cloth face mask use during maximal aerobic fitness test.